Molecular Evidence for the Presence of Rickettsia Felis in the Feces of Wild-living African Apes - Keita, Alpha Kabinet; Socolovschi, Cristina; Ahuka-Mundeke, Steve; Ratmanov, Pavel; Butel, Christelle; Ayouba, Ahidjo; Inogwabini, Bila-Isia; Muyembe-Tamfum, Jean-Jacques; Mpoudi-Ngole, Eitel; Delaporte, Eric; Peeters, Martine; Fenollar, Florence; et al. (PLOS ONE, 2013)
Background Rickettsia felis is a common emerging pathogen detected in mosquitoes in sub-Saharan Africa. We hypothesized that, as with malaria, great apes may be exposed to the infectious bite of infected mosquitoes and release R. felis DNA in their feces. Methods We conducted a study of 17 forest sites in Central Africa, testing 1,028 fecal samples from 313 chimpanzees, 430 gorillas and 285 bonobos. The presence of rickettsial DNA was investigated by specific quantitative real-time PCR. Positive results were confirmed by a second PCR using primers and a probe targeting a specific gene for R. felis. All positive samples were sequenced. Results Overall, 113 samples (11%) were positive for the Rickettsia-specific gltA gene, including 25 (22%) that were positive for R. felis. The citrate synthase (gltA) sequence and outer membrane protein A (ompA) sequence analysis indicated 99% identity at the nucleotide level to R. felis. The 88 other samples (78%) were negative using R. felis-specific qPCR and were compatible with R. felis-like organisms. Conclusion For the first time, we detected R. felis in wild-living ape feces. This non invasive detection of human pathogens in endangered species opens up new possibilities in the molecular epidemiology and evolutionary analysis of infectious diseases, beside HIV and malaria.